Emergence and Containment of Canine Influenza Virus A(H3N2), Ontario, Canada, 2017–2018 - J. Scott Weese; Maureen E.C. Anderson; Yohannes Berhane; Kathleen F. Doyle; Christian Leutenegger; Roxanne Chan; Michelle Chiunti; Katerina Marchildon; Nicole Dumouchelle; Theresa DeGelder; Kiera Murison; Catherine Filejksi; et al. (Emerging Infectious Diseases, 2019)
Canine influenza virus (CIV) A(H3N2) was identified in 104 dogs in Ontario, Canada, during December 28, 2017–October 30, 2018, in distinct epidemiologic clusters. High morbidity rates occurred within groups of dogs, and kennels and a veterinary clinic were identified as foci of infection. Death attributable to CIV infection occurred in 2 (2%) of 104 diagnosed cases. A combination of testing of suspected cases, contact tracing and testing, and 28-day isolation of infected dogs was used, and CIV transmission was contained in each outbreak. Dogs recently imported from Asia were implicated as the source of infection. CIV H3N2 spread rapidly within groups in this immunologically naive population; however, containment measures were apparently effective, demonstrating the potential value of prompt diagnosis and implementation of CIV control measures.